Bulk-Saving Way to Implement Health Education Development Paradigm - Гаращук, О. В.; Куценко, В. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article focuses on the essence of health care for the nation’s socio-economic development of the country. In this regard, the article focuses on the health of the younger generation, the youth. The factors that adversely affect health are brought up in the article. Special attention is given to the relevant issues of the educational environment, an important component of which is the availability of the necessary infrastructure for the preservation and strengthening of health of pupils, students, as well as providing educational functions of education. We give the main ways to ensure the implementation of health-saving educational paradigm of development requirements.